Mobilities in the Swiss Alps: Circulation and Rootedness - Friedli, Andrea; Boscoboinik , Andrea (Quaderns de l'Institut Català d'Antropologia, 2023)
In this contribution, we wish to shed light on narratives and imaginaries of new inhabitants in two Swiss mountain regions, concerning place and belonging, and how these are shaped by concerns of (im)mobilities, circulation and rootedness. Taking into consideration the diverse profiles of people living in the mountains, our aim is to analyse the processes of attachment to place, as enacted both by inhabitants who have migrated for labour reasons and by lifestyle migrants. How do different types of mobilities, and ways of belonging by new inhabitants of urbanised mountain resorts influence their strategies of making sense of place and (local) community? What expectations do both the newcomers and the residents established for several generations carry about each other and the place? How do social processes not only affect people “on the move”, but also the localities that are travelled, visited, inhabited, and invested by these people? We will see that the economic, financial and social backgrounds of the mountain inhabitants have a strong impact on their regimes of mobility, but also that place-attachment, rootedness and commitment to the local community have an influence, and that these vary in the intersection of gender, origin, and social class dimensions.